High Rate of Bacterial Contamination on Healthcare Worker’s Mobile Phone and Potential Role in Dissemination of Healthcare-Associated Infection at Debre Berhan Referral Hospital, North Shoa Zone, Ethiopia - Asfaw T; Genetu D (Dove Medical Press, 2021)
Tsegahun Asfaw, Deribew Genetu Department of Medical Laboratory Science, Debre Berhan University, Debre Berhan, EthiopiaCorrespondence: Tsegahun Asfaw Email tsegahun.asfaw12@gmail.comBackground: Mobile Phone (MP) handling by healthcare workers (HCWs) in hospital is an open breeding place for the transmission of bacteria and healthcare-associated infection (HCAI). This HCAI is a huge problem to the healthcare system worldwide.Methods: A laboratory-based cross-sectional study design was conducted from January 2020 to January 2021 in Debre Berhan Referral Hospital, North Shoa Zone, Ethiopia. A total of 65 swab samples were collected from HCWs mobiles phone. Other important data were collected using a self-administered questionnaire. The collected samples were processed for bacteriological identification and drug susceptibility testing. Data obtained were entered and cleaned into MS Excel spreadsheet and analyzed using SPSS version 21.Results: From the total of 65 swab sample, 84 bacterial isolates were detected. Of these bacterial isolates, 46.4% were Gram-positive bacteria while 53.6% were Gram-negative bacteria. The overall MDR prevalence was found to be 42.9%. The proportion of MP contamination was higher in males (67.9%) and the age groups of 20– 35 years (50%). All the MP carried by HCWs was contaminated with at least one bacterial pathogen. The high rate of MP contamination was observed in the intensive care unit (ICU) (22.6%) followed by surgical ward (17.8) and laboratory rooms (17.8%). The rate of bacterial contamination of MP was higher among HCWs working in ICU, who did not disinfect or clean their phone regularly and who did not wash their hands regularly.Conclusion: Healthcare worker’s MP was contaminated with pathogenic bacteria. Since MP could serve as a vehicle and a reservoir for pathogenic bacteria, HCWs should be aware of the public health risks of HCAI, and appropriate intervention mechanisms should be practiced to reduce the burden and cross-transmission.Keywords: bacterial contamination, mobile phone, healthcare worker